Effects of Different Protein and Energy Contents of the Diet on Growth Performance and Hormonal Parameters in Two Commercial Broiler Strains - Rahimi, G.; Hassanzadeh, M. (International Journal of Poultry Science, 2007)
The present study was carried out to investigate the influence of energy and protein contents of the diet on growth performance and to evaluate further interactions of dietary manipulation and genotype on endocrine parameters in broiler chickens. 1200 day-old male and female broiler chicks from 2 commercial broiler strains (Hybro and Ross) were fed ad libitum from day 1 onwards by 4 different diets either with a high or low energy combined with a high or low crude protein content. Body weight and feed intake were measured weekly. Venous blood samples were taken (10 birds/sex /line/diet group) weekly from day 14 on, for plasma Growth Hormone (GH), Triiodotyronine (T3) and Thyroxin (T4) content. Relative growth rate was higher in broiler chickens which fed the low energy diet compared to high energy diet during the first week of age, while from week 1 on, a reverse effect of energy on relative growth rate was found. The effect of energy and protein on feed intake was significant (p